2021
DOI: 10.1016/j.jpain.2021.03.145
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sickness Absence in a Clinical Population With Chronic Pain

Abstract: Chronic pain-related sickness absence is an enormous socioeconomic burden globally.Optimized interventions are reliant on a lucid understanding of the distribution of social insurance benefits and their predictors. This register-based observational study analyzed data for a 7-year period from a population-based sample of 44,241 chronic pain patients eligible for interdisciplinary treatment (IDT) at specialist clinics. Sequence analysis was used to describe the sickness absence over the complete period and to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…In what follows, we describe the support for the relationship of the confounders to the intervention and the outcome. History of sickness absence is both an indicator of IDT and a strong predictor of future sickness absence, while policy differences result in geographical and temporal variations of the two (Bramberg et al, 2015;Dorner et al, 2015;LoMartire et al, 2021;Ropponen et al, 2020;Wallman et al, 2009). With respect to sociodemographics, both healthcare consumption and sickness absence reportedly increase with age and female sex, while socioeconomic status is inversely associated with both the likelihood to receive adequate healthcare and sickness absence (Adler & Newman, 2002;Cylus et al, 2011;Dorner et al, 2015;Lager et al, 2019;LoMartire et al, 2021;Mastekaasa & Melsom, 2014;Moscelli et al, 2018;Patton & Johns, 2007;Ropponen et al, 2020;Wallman et al, 2009;Wang et al, 2013).…”
Section: Causal Structurementioning
confidence: 99%
See 2 more Smart Citations
“…In what follows, we describe the support for the relationship of the confounders to the intervention and the outcome. History of sickness absence is both an indicator of IDT and a strong predictor of future sickness absence, while policy differences result in geographical and temporal variations of the two (Bramberg et al, 2015;Dorner et al, 2015;LoMartire et al, 2021;Ropponen et al, 2020;Wallman et al, 2009). With respect to sociodemographics, both healthcare consumption and sickness absence reportedly increase with age and female sex, while socioeconomic status is inversely associated with both the likelihood to receive adequate healthcare and sickness absence (Adler & Newman, 2002;Cylus et al, 2011;Dorner et al, 2015;Lager et al, 2019;LoMartire et al, 2021;Mastekaasa & Melsom, 2014;Moscelli et al, 2018;Patton & Johns, 2007;Ropponen et al, 2020;Wallman et al, 2009;Wang et al, 2013).…”
Section: Causal Structurementioning
confidence: 99%
“…History of sickness absence is both an indicator of IDT and a strong predictor of future sickness absence, while policy differences result in geographical and temporal variations of the two (Bramberg et al, 2015;Dorner et al, 2015;LoMartire et al, 2021;Ropponen et al, 2020;Wallman et al, 2009). With respect to sociodemographics, both healthcare consumption and sickness absence reportedly increase with age and female sex, while socioeconomic status is inversely associated with both the likelihood to receive adequate healthcare and sickness absence (Adler & Newman, 2002;Cylus et al, 2011;Dorner et al, 2015;Lager et al, 2019;LoMartire et al, 2021;Mastekaasa & Melsom, 2014;Moscelli et al, 2018;Patton & Johns, 2007;Ropponen et al, 2020;Wallman et al, 2009;Wang et al, 2013). As emphasized in ICD-11, emotional distress and pain interference in everyday activities are critical dimensions of chronic pain, and both of these are positively associated with both IDT and sickness absence (Gerdle et al, 2011;Hallman et al, 2019;Svebak & Halvari, 2018;Treede et al, 2019).…”
Section: Causal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…One of the researchers (CT) will enrol and randomise participants who have given informed consent (S3) to participate in the study to either the intervention or control group. As sick leave history is a strong predictor for future sick leave45 participants will be stratified into high or low sick leave history based on self-reported number of sick leave days during the year before IPRP. It has been shown that patients with low sick leave history to a larger extent are younger, have an employment, higher education and are more confident regarding recovery 45.…”
Section: Methods and Analysismentioning
confidence: 99%
“…As sick leave history is a strong predictor for future sick leave45 participants will be stratified into high or low sick leave history based on self-reported number of sick leave days during the year before IPRP. It has been shown that patients with low sick leave history to a larger extent are younger, have an employment, higher education and are more confident regarding recovery 45. Participants will therefore be divided in high (total number of gross sick leave days ≥70) or low sick leave absence45 and then randomised to intervention or control group.…”
Section: Methods and Analysismentioning
confidence: 99%